Teaching approach for indigenous people: an empirical study from Pahang, Malaysia - Borham, Abd Hadi; Huda, Miftachul; Rasid, Muhammad Saifullah Abdul; Rahim, Mohamad Marzuqi Abdul; Hamid, Nurhanis Zahidah Abdul (Intelektual Pustaka Media Utama, 2024)
This study aims to examine the approach in teaching practice to muallaf (Muslim indigenous people: orang asli) and the factors of attraction toward the acceptance of Islamic understanding among them. The study was conducted at the village of muallaf orang asli at Paya Sendayan, Temerloh Pahang, Malaysia. Design of this study are using the qualitative methods. Data were collected by observation and selected informant interviews based on purposive sampling methods. Data were analysed using the thematic methods. The results of the study found that the approach in teaching practice to muallaf orang asli is syarah (explanation) and discussion presented through storytelling, stimulation method and talaqqi musyafahah (face to face). Meanwhile, the results of the attraction factors toward the acceptance of teaching and learning among muallaf orang asli are aspect of reward, facilities, understanding and skills of teachers or educators for the socio-culture and role model shown by teachers or educators as well as the Muslim community nearby the living community. The findings of this study show that the teaching and learning of muallaf orang asli should be organized systematically in line with the factors of attraction in order to increase interest and earnestly.